Matorralización de la dehesa: implicaciones en la productividad total del sistema (VI Congreso Forestal Español, 2013)
La dehesa ha sido tradicionalmente un sistema muy diverso en el que, además de los pastos naturales y cultivos periódicos, han existido manchas de monte y zonas de arbolado claro con matorral. Existen cada vez más evidencias científicas y técnicas del papel positivo que puede jugar el matorral en la dehesa, principalmente en la regeneración del arbolado. Sin embargo, la matorralización de la dehesa puede tener consecuencias en la productividad total del sistema. El objetivo de este ensayo es evaluar los efectos de la matorralización en los diferentes recursos forrajeros de la dehesa: producción de bellota, ramón (proveniente del arbolado y matorral) y pasto herbáceo, así como sobre la Energía metabolizable. El estudio se ha enfocado en dos tipos de matorral que presentan comportamientos muy contrastados en términos de uso de recursos edáficos: jaral (Cistus ladanifer L.) y retamal (Retama sphaerocarpa (L.) Boiss.). Para ello, se tomaron muestras de los diferentes recursos forrajeros entre 2007 y 2010 en 40 dehesas. La presencia de jara redujo la productividad total de la dehesa, debido al efecto negativo que provoca sobre la producción de bellotas y pasto herbáceo y que no lleva a compensarse con el ramoneo. En cambio, se observó un efecto facilitador de la retama que dio lugar a una mejora en la productividad del sistema.
The following values have no corresponding Zotero field: periodical: VI Congreso Forestal Español pub-location: Vitoria

Development and application of bio-economic modelling to compare silvoarable, arable, and forestry systems in three European countries - a. R. Graves; Burgess, P. J. J.; Palma, J. H. N. H. N.; Herzog, F.; Moreno, G.; Bertomeu, M.; Dupraz, C.; Liagre, F.; Keesman, K.; van der Werf, W.; de Nooy, a Koeffeman; van den Briel, J. P. P.; et al. (Ecological Engineering, 2007)
Silvoarable agroforestry could promote use of trees on farms in Europe, but its likely effect on production, farm proﬁtability, and environmental services is poorly understood. Hence, from 2001 to 2005, the Silvoarable Agroforestry for Europe project developed a systematic process to evaluate the biophysical and economic performance of arable, forestry, and silvoarable systems in Spain, France, and The Netherlands. A biophysical model called “Yield-SAFE” was developed to predict long-term yields for the different systems and local statistics and expert opinion were used to derive their revenue, costs, and pre- and post-2005 grant regimes. These data were then used in an economic model called “Farm-SAFE” to predict plot- and farm-scale proﬁtability. Land equivalent ratios were greater than one, showing Yield-SAFE predicted that growing trees and crops in silvoarable systems was more productive than growing them separately. Pre-2005 grants in Spain and The Netherlands penalised silvoarable systems, but post-2005 grants were more equitable. In France, walnut and poplar silvoarable systems were consistently the most proﬁtable system under both grant regimes. In Spain, holm oak and stone pine silvoarable systems were the least proﬁtable system under pre-2005 grants, but only marginally less proﬁtable than arable systems under post-2005 grants. In The Netherlands, low timber values and the opportunity cost of losing arable land for slurry manure application made silvoarable and forestry systems uncompetitive with arable systems under both grant regimes.
Keywords: Agroforestry; Arable; Biophysical; Economics; Farm-SAFE; Forestry; Modelling; Poplar; Silvoarable; Temperate; Walnut; Yield-SAFE

Development and application of bio-economic modelling to compare silvoarable, arable, and forestry systems in three European countries (Ecological Engineering, 2007)
Silvoarable agroforestry could promote use of trees on farms in Europe, but its likely effect on production, farm proﬁtability, and environmental services is poorly understood. Hence, from 2001 to 2005, the Silvoarable Agroforestry for Europe project developed a systematic process to evaluate the biophysical and economic performance of arable, forestry, and silvoarable systems in Spain, France, and The Netherlands. A biophysical model called “Yield-SAFE” was developed to predict long-term yields for the different systems and local statistics and expert opinion were used to derive their revenue, costs, and pre- and post-2005 grant regimes. These data were then used in an economic model called “Farm-SAFE” to predict plot- and farm-scale proﬁtability. Land equivalent ratios were greater than one, showing Yield-SAFE predicted that growing trees and crops in silvoarable systems was more productive than growing them separately. Pre-2005 grants in Spain and The Netherlands penalised silvoarable systems, but post-2005 grants were more equitable. In France, walnut and poplar silvoarable systems were consistently the most proﬁtable system under both grant regimes. In Spain, holm oak and stone pine silvoarable systems were the least proﬁtable system under pre-2005 grants, but only marginally less proﬁtable than arable systems under post-2005 grants. In The Netherlands, low timber values and the opportunity cost of losing arable land for slurry manure application made silvoarable and forestry systems uncompetitive with arable systems under both grant regimes.

Silvoarable Systems in Europe – Past, Present and Future Prospects - Eichhorn, M. P.; Paris, P.; Herzog, F.; Incoll, L. D.; Liagre, F.; Mantzanas, K.; Mayus, M.; Moreno, G.; PAPANASTASIS, V. P.; Pilbeam, D. J.; Pisanelli, A.; Dupraz, C. (Agroforestry Systems, 2006)
Mixed systems of agriculture incorporating combinations of trees and crops have formed key elements of the landscape of Europe throughout historical times, and many such systems continue to function in the present day. In many cases they represent formerly widespread traditional systems in decline and a number have already become extinct or exist only in a threatened state. The causes are both practical and economic. The agricultural subsidy regime within the European Union is presently unfavourable towards silvoarable practices, which has been a major factor in their recent decline. The silvoarable systems of Europe can be split into two classes according to location – northern Europe and the Mediterranean. The latter contains not only a greater area of silvoarable cultivation, but also a greater diversity of systems due to the broader range of commercial tree and crop species grown. In general, the systems of northern Europe are limited by light, whilst those of the Mediterranean are limited by the availability of water. Mixed systems of agriculture present an opportunity for future European rural development and have the potential to contribute towards the increased sustainability of agriculture and enhancement of biodiversity, whilst preserving landscapes that are both culturally important and aesthetically pleasing. A better understanding of the legacy of traditional silvoarable systems, combined with the formulation of a consistent deﬁnition and speciﬁc European policy towards them will be invaluable in ensuring that the beneﬁts of mixed agriculture are fully exploited in the future.
Keywords: Dehesa; hauberg; intercropping; orchards; pre-vergers; Streuobst; Timber

Soil nutrient status and forage yield at varying distances from trees in four dehesas in Extremadura, Spain - Obrador, J. J.; Moreno, G. (Silvopastoralism and Sustainable Land Management: Proceedings of an International Congress on Silvopastoralism and Sustainable Management Held in Lugo Spain, in April 2004, 2006)
The aim of this study was to understand the effect of holm-oak (Quercus ilex) on the soilnutrient concentration and its consequence on the yield of understory forage (Avena sativa) in four dehesas of CW-Spain. The soils of the dehesas varied in soil fertility (chromic Luvisols and Achrisols, and eutric Leptosols). Forage dry-matter yields were determined from 1-m2 sample plots at distances ranging from 2 to 20 m from the tree (9 trees per farm and year). Soil samples (0-30 cm depth) were also collected from the same sampling locations, and were analysed for pH, Electrical Conductivity, organic C, CEC, total-N, available N and base cations. Soil analysis results showed that the most of the values increased in the vicinity of the tree: organic C, total-N, CEC and exchangeable Ca2+ and K+. Differences in forage yield were mainly explained by fertilization dosage, light availability (estimated from Montero and Moreno, 2004) and soil CEC. In more fertile soils, forage production was negatively effected by the presence of the trees, as a consequence of light reduction (Competence), while in more oligotrophic soils, forage production was positively affetced by trees (Facilitation).
The following values have no corresponding Zotero field: periodical: Silvopastoralism and Sustainable Land Management: Proceedings of an International Congress on Silvopastoralism and Sustainable Management Held in Lugo Spain, in April 2004
Keywords: competence; Dehesa; Facilitation; forage yield; soil nutrient heterogeneity